The Participatory Aspect of Eco-Fashion - Zhang, Dongcan; Lahoda, Oksana (HUDPROM: The Ukrainian Art and Design Journal, 2025)
This study analyses the causal relationships between the evolution of design practices and the transformation of artistic and creative concepts within the socio-cultural dynamics of the 20th and early 21st centuries. Particular emphasis is placed on the centrality of human-centred design, the content of which has undergone substantial shifts in recent decades, resulting in the institutionalisation of participatory design practices. The article identifies the preconditions for the emergence of participatory approaches in clothing design, conceptualising them as a new form of designer–consumer interaction founded on shared recognition of sustainable development imperatives, demand for eco-fashion, and the creation of environmentally responsible products. The idea of eco-friendly clothing, first articulated through the ideology and lifestyle of the hippie subculture of the 1970s, has retained its relevance, though subjected to multiple reinterpretations and transformations from a subcultural trend to an autonomous sector of the fashion industry characterised by innovation, technological advancement, and process digitalisation. It is demonstrated that the processes of cultural massification and globalisation have amplified the role of the consumer as an active subject within the design process. The gradual transition from standardised products of mass culture to individualised and personalised designer apparel is shown to constitute the basis for the participatory dimension of design, facilitating the dissemination of ecological thinking and corresponding consumer demands. Furthermore, the shift from standardised mass-produced goods to individualised, personalised clothing has laid the foundation for participatory design, supporting the spread of ecological thinking and related consumer demands. Finally, the study identifies the key principles of participatory design and outlines the main concepts defining sustainable fashion development.